Educação linguística em português como língua estrangeira para fins acadêmicos: qual mundo sustentar? - Nascimento, Mariana Ruiz (2024)
In this work, I address linguistic education aimed at the production of teaching materials, from a decolonial and sustainable perspective. I relate these aspects based on my professional and academic background and my body, based on my experiences and some discomforts that I transformed into research concerns. The objective of the research was to think of alternatives for linguistic education in order to deconstruct oppressive linguistic practices that are complicit with coloniality; and to discuss the production of a Portuguese as a Foreign Language textbook for academic purposes when we consider the philosophies and epistemologies of authors from the Global South and, more importantly, from ancestral traditions of collective existence and connected to the Earth (Krenak, 2019, 2020, 2022; Santos, 2023; Brum, 2021). When reflecting theoretically about the activities for the textbook in an Open Educational Resource (OER) format, I argue that to educate linguistically with a view to sustainability in foreign languages implies applying a sustainability device that functions at the same time as a critical lens and as a propositional tool. To this end, as a methodology, I carried out an autoethnography to reflect on my own body as a researcher and teacher of English and Portuguese and to prepare the teaching material, in which multiple identifications and reflections meet and conflict. I used discourse analysis to analyze the field diary and the cultural artifacts (Pêcheux, 1983, 1991, 2009; Bakhtin, 2016), aiming to understand the effects and displacements of meanings and discursive positions. Therefore, it is a qualitative proposal with a descriptive and interpretative approach (Gerhardt; Silveira, 2009; Merriam; Tisdell, 2016; Creswell; Creswell, 2018). I situate this work in the field of Brazilian Applied Linguistics, which is critical, transgressive and inter/trans/indisciplinary (Celani, 1992, 2000; Moita Lopes, 2006; Signorini, 2006) and, throughout the work, I also consider contributions from researchers who identify with decolonial thinking (Quijano, 2007, 2000; Maldonado-Torres, 2007 Mignolo, 2003). Finally, the research allowed new perspectives on the process of developing language teaching materials, mainly to show that it inevitably reveals the positions of the material's producer and that it is not a neutral process in which there may be a distance between the author and the product. In the case of this research, it was a process that called me to reflect and fulfill my political responsibility as a foreign language teacher.